Updated recommendations of the German Society for Rheumatology for the care of patients with inflammatory rheumatic diseases in times of SARS-CoV-2: methodology, key messages and justifying information - Schulze-Koops, Hendrik; Krüger, Klaus; Hoyer, Bimba Franziska; Leipe, Jan; Iking-Konert, Christof; Specker, Christof (Rheumatology, 2021)
A few days after the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was declared a pandemic, the German Society for Rheumatology (DGRh) compiled the first group of recommendations for the care of patients with inflammatory rheumatic diseases in light of SARS-CoV-2/coronavirus disease 2019 (COVID-19). These first recommendations were based on an expert consensus and were largely non-evidence-based. Now that the first scientific data from registries, cross-sectional studies, case reports and case series are available, the DGRh has developed a timely update. This update is based on a literature search of publications available through 15 June 2020 and addresses preventive measures (such as hygiene measures or vaccinations) and the use of immunomodulatory/immunosuppressive drugs. Driven by the commitment to let patients benefit from these new evidence-based recommendations as quickly as possible, the DGRh published the update in German on its homepage and in the Zeitschrift für Rheumatologie immediately after completion. Here we report the key recommendations to make them available to the international community, provide the scientific methodology used to develop the recommendations, give additional thoughts and advice for the management of patients with rheumatic diseases during the COVID-19 pandemic and discuss our recommendations in the context of other international recommendations.